Metastatic Breast Cancer to the Gastrointestinal Tract: Report of Five Cases and Review of the Literature - Massimo Ambroggi; Elisa Maria Stroppa; Patrizia Mordenti; Claudia Biasini; Adriano Zangrandi; Emanuele Michieletti; Elena Belloni; Luigi Cavanna (International Journal of Breast Cancer)
Luminal gastrointestinal (GI) metastases from breast cancer are rare, reports are fragmentary and poor. The purposes of this study are to assess the gastrointestinal involvement from breast cancer in a retrospective study at a single institution and reviewing the related literature. Between January 2007 and December 2011 a total of 980 patients with breast cancer were treated at our institution, patients’ records and report database were analysed. Institutional Review Board approval was obtained for this study. A search of the literature using PubMed, CancerLit, Embase, was performed. Selected for the present review were papers published in English before June 2012. Five of 980 patients (0.5%) showed gastrointestinal metastases from breast cancer, 3 patients had gastric involvement, 1 jejunum, and 1 rectum. Reviewing the literature, 206 patients affected by gastrointestinal metastasis from breast cancer were identified: the most frequent site of metastasis was the stomach (60%). The majority of the patients underwent chemotherapy and endocrine therapy, someone surgery and radiotherapy. GI metastases from breast cancer are rare, but possible, and a very late recurrence can also occur. Cyto-histological diagnosis is mandatory, to differentiate GI metastases from breast cancer to other diseases and to allow an adequate treatment.